2002
DOI: 10.1016/s0014-5793(02)03005-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of C‐terminal cytoplasmic domain of the AT2 receptor in ligand binding and signaling

Abstract: A stop codon at position 322 was introduced to generate a truncated, C-terminal-deleted AT2 receptor. Expression studies in Xenopus oocytes showed that C-terminal-deleted AT2 had reduced a⁄nity to [ 125 I]angiotensin II (K d = 1.7 nM) and enhanced binding of the AT2-speci¢c peptidic ligand [ 125 I]CGP42112A (K d = 0.097 nM). AT2 activation by angiotensin II resulted in reduction of cGMP levels in oocytes and this reduction was further enhanced by C-terminal deletion, implying that the C-terminus may have a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…This was suggested by the observation that ATIP1 and AT2 attenuate RTK autophosphorylation, and by recent studies showing that ErbB3, a member of the EGF receptor family, interacts with the AT2 receptor C-terminal portion (20,21). Experiments performed on transfected CHO-hAT2 and COS-AT2 cells failed, however, to detect direct interaction between ATIP1 and the EGF receptor or the insulin receptor ␤-chain, either at basal levels or after stimulation with Ang II, EGF, or insulin (data not shown).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This was suggested by the observation that ATIP1 and AT2 attenuate RTK autophosphorylation, and by recent studies showing that ErbB3, a member of the EGF receptor family, interacts with the AT2 receptor C-terminal portion (20,21). Experiments performed on transfected CHO-hAT2 and COS-AT2 cells failed, however, to detect direct interaction between ATIP1 and the EGF receptor or the insulin receptor ␤-chain, either at basal levels or after stimulation with Ang II, EGF, or insulin (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…ATRAP is one such example of a novel protein that selectively interacts with the AT1 receptor C terminus and down-regulates its activity (18,19). Regarding the AT2 receptor, recent studies have documented a direct interaction of its C-terminal tail with ErbB3, a member of the EGF receptor family (20,21), and with the transcription factor promyelocytic zinc finger containing protein (PLZF) abundantly expressed in the heart (22).…”
mentioning
confidence: 99%
“…The currents generated by cloned AT1 and AT2 expressed in the oocytes are similarly mediated by gating of those chloride channels. These results were somewhat unexpected because the rAT2 receptors are known to reduce the intracellular levels of cGMP [29]. Nonetheless, in Xenopus oocytes the cloned receptor coupled to the DAG/IP 3 pathway and generated the characteristic oscillatory currents.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, recent experimental studies have shown the existence of proteins interacting with Ang II receptors, screened by the yeast-based two-hybrid protein-protein interaction assay technique, and have also revealed their functions. [5][6][7][8][9][10][11][12] For the AT 1 receptor, AT 1 receptor-associated protein could act as a negative regulator in AT 1 receptor-mediated cell proliferation and vascular remodeling, at least in part by the enhancement of AT 1 receptor internalization. 13,14 On the other hand, the AT 2 receptor-interacting protein seems to act as a novel early component of the growth inhibitory signaling cascade of the AT 2 receptor.…”
Section: New Paradigm Shift Of Renin-angiotensin Systemmentioning
confidence: 99%